Resilience among bereaved college students: Indicators, facilitators, and barriers. Issue 2 (7th February 2023) - Plocha, Aleksandra; Modrak, Stephanie; Hoopes, Molly; Donahoe, Amanda; Priest, Amanda
Abstract: We adopted a resilience framework to gain a deeper understanding of the specific ways that grief impacts college students and identify specific ways that counselors can promote resilience among this population. Data from interviews with 10 college students were analyzed using grounded theory. Three categories of themes related to promoting resilience among bereaved college students were extracted: indications of what needs to change to be doing OK, factors that facilitate becoming OK, and barriers to the grieving process and becoming OK. The facilitators for and barriers to achieving these indicators of resilience are discussed in the context of navigating bereavement as a college student. Specific recommendations are made for counselors and college personnel.